ANALYSIS OF THE POLITICAL DISCOURSE IN THE PREELECTION CAMPAIGNS IN REPUBLIC OF MACEDONIA AND IN USA (Journal of Contemporary Philology, 2018)
This article’s objective is to conduct a critical discourse analysis of political speeches in  the  Republic  of  Macedonia  and  the  USA.  This  research  gives  an  insight  into  the manipulative   function   of   language   and   it   shows   how   politicians   achieve   this manipulation.  For  this  purpose,  eight  political  speeches  have  been  analyzed:  four speeches given by Macedonian politicians (Gruevski, Zaev, Ivanov, and Pendarovski) and  four  given  by  American  politicians  (Obama,  Romney,  Bush,  and  Kerry).  The analysis covers the pragmatic aspect, it examines how much attention the politicians pay toexpressing  their  own  opinion  and  political  stances  and  how  they  include  the audience in their speech. The focus of the analysis is on the personal pronouns.
Keywords: political discourse; linguistic manipulation; campaign speeches; personal pronouns